Pengembangan Clinical Pathway Stroke Hemoragik Berbasis 3S (SDKI, SLKI, SIKI) - Adi Sukrisno; Nursalam Nursalam; Ferry Efendi; Asroful Hulam Zamroni (Journal of Telenursing (JOTING), 2023)
This study aims to develop a clinical pathway for hemorrhagic stroke patients based on the 3S (SDKI, SLKI, SIKI). The method used is Research and Development with stages including literature study, observation evaluation, validity and reliability testing, and Focus Group Discussion (FGD). The research results show that developing a 3S-based hemorrhagic stroke clinical pathway is by clinical practice guidelines and service quality. The results of Pearson's product-moment correlation test are <0.514, and the reliability of the Cronbach alpha test is 0.906. Conclusion: The development of a 3S-based hemorrhagic stroke clinical pathway was prepared with nursing diagnoses, including ineffective airway clearance, decreased intracranial adaptive capacity, acute pain, impaired physical mobility, and risk of fluid imbalance. The development of a 3S-based hemorrhagic stroke clinical pathway is generally in good categories in terms of Functionality, Efficiency, and Usability so that it can be recommended for use by nurses and can improve the quality of hospital services. Keywords: Clinical Pathway, SDKI, SIKI, SLKI, Hemorrhagic Stroke